Analyzing the causal relationship between lipid-lowering drug target genes and epilepsy: a Mendelian randomization study - Huang, Shicun; Liu, Yuan; Zhang, Yi; Wang, Yiqing; Gao, Ya; Li, Runnan; Yu, Lidong; Hu, Xiaowei; Fang, Qi (Frontiers in Neurology, 2024)
Background: Previous research has yielded conflicting findings on the link between epilepsy risk and lipid-lowering medications. The aim of this study is to determine whether the risk of epilepsy outcomes is causally related to lipid-lowering medications predicted by genetics.We used genetic instruments to proxy the exposure of lipid-lowering drugs, employing variants within or near genes targeted by these drugs and associated with low-density lipoprotein (LDL cholesterol) from a genome-wide association study.These variants served as controlling factors. Through drug-target Mendelian 2 / 15 randomization, we systematically assessed the impact of lipid-lowering medications, including HMGCR inhibitors, PCSK9 inhibitors, and NPC1L1 inhibitors, on epilepsy.The analysis demonstrated that a higher expression of HMGCR was associated with an elevated risk of various types of epilepsy, including all types [OR= 1.17, 95% CI:1.03 to 1.32, P = 0.01], focal epilepsy [OR=1.24, 95% CI:1.08 to 1.43, P = 0.003],and focal epilepsy with lesions other than hippocampal sclerosis [OR=1.05, 95% CI:1.01 to 1.10, P = 0.02]. The risk of juvenile absence epilepsy (JAE) was also associated with higher expression of PCSK9 [OR=1.06, 95% CI: 1.02 to 1.09, P = 0.002]. For other relationships, there was no reliable supporting data available.The drug-target MR investigation suggests a possible link between reduced epilepsy vulnerability and HMGCR and PCSK9 inhibition.